Retrospective analysis supports algorithm as efficient diagnostic approach to treatable intellectual developmental disabilities - Sayson, Bryan; Popurs, Marioara Angela Moisa; Lafek, Mirafe; Berkow, Ruth; Stockler-Ipsiroglu, Sylvia; van Karnebeek, Clara D.M. (Molecular genetics and metabolism, 2015)
Intellectual developmental disorders (IDD11Abbreviations:Intellectual developmental disorders (IDD)Inborn Errors of Metabolism (IEM)Treatable Intellectual Disability Endeavour (TIDE)Whole Exome Sequencing (WES).), characterized by a significant impairment in cognitive function and behavior, affect 2.5% of the population and are associated with considerable morbidity and healthcare costs. Inborn errors of metabolism (IEM) currently constitute the largest group of genetic defects presenting with IDD, which are amenable to causal therapy. Recently, we created an evidence-based 2-tiered diagnostic protocol (TIDE protocol); the first tier is a ‘screening step’ applied in all patients, comprising routinely performed, wide available metabolic tests in blood and urine, while second-tier tests are more specific and based on the patient's phenotype. The protocol is supported by an app (www.treatable-ID.org). To retrospectively examine the cost- and time-effectiveness of the TIDE protocol in patients identified with a treatable IEM at the British Columbia Children's Hospital. We searched the database for all IDD patients diagnosed with a treatable IEM, during the period 2000–2009 in our academic institution. Data regarding the patient's clinical phenotype, IEM, diagnostic tests and interval were collected. Total costs and time intervals associated with all testing and physician consultations actually performed were calculated and compared to the model of the TIDE protocol. Thirty-one patients (16 males) were diagnosed with treatable IDD during the period 2000–2009. For those identifiable via the 1st tier (n=20), the average cost savings would have been $311.17 CAD, and for those diagnosed via a second-tier test (n=11) $340.14 CAD. Significant diagnostic delay (mean 9months; range 1–29 months) could have been avoided in 9 patients with first-tier diagnoses, had the TIDE protocol been used. For those with second-tier treatable IDD, diagnoses could have been more rapidly achieved with the use of the Treatable IDD app allowing for specific searches based on signs and symptoms. The TIDE protocol for treatable forms of IDD appears effective reducing diagnostic delay and unnecessary costs. Larger prospective studies, currently underway, are needed to prove that standard screening for treatable conditions in patients with IDD is time- and cost-effective, and most importantly will preserve brain function by timely diagnosis enabling initiation of causal therapy. •Retrospective TIDE protocol study in 31 IDD patients with treatable IEMs (2000–2009).•Twenty treatable IEMs identifiable via 1st-tier routine metabolic screening tests.•TIDE protocol implementation would have saved costs in all ($311–340CAD).•Diagnostic delay could have been shortened with TIDE protocol and Treatable IDD app.